HE SACCHAROMYCES BOULARD II, AS A POTENTIAL PROBIOTIC FOR INNOVATIVE FOODS - S. A. Ryabtseva; S. N. Sazanova; A. A. Dubinina (Современная наука и инновации, 2022)
Biochemistry, genetics and taxonomy of Saccharomyces boulardii are considered; data on the probiotic properties of this yeast to produce new functional additives and foods are systematized.